Research Note: Rethinking Feminist Engagements with the State and Wage Labour - Alessandrini, Donatella (feminists@law, 2014)
In this paper I reflect on recent attempts by feminist economists to engage with post-Keynsian policies aimed at the socialisation of investment, in particular the proposal for the government to act at once as the Employer of Last Resort (ELR) and a social provider. Such an engagement seems to depart from feminist autonomists' critique of the wage society, their refusal to place reformist demands on the state and their emphasis on the collectivisation of social reproduction. Drawing on earlier explorations by Italian feminists of the dynamic interaction between labour and value, I suggest that these two approaches might not be as different as they first appear: at stake for both is a challenge to capitalist value through the promotion of arrangements able to instantiate alternative processes of valorisation.